Outcome pattern of mycophenolate mofetil in combination with low dose steroid in Graves’ orbitopathy - Islam, Mazharul; Aich, Partha Pulak; Kabir, Shawkat; Khan, Murshed Ahamed; Mustari, Marufa; Selim, Shahjada; Fariduddin, Md. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Graves' orbitopathy (GO) is a debilitating autoimmune condition associated with thyroid disease. Despite corticosteroids being the primary treatment, many patients show inadequate responses or relapse. Aim: To evaluate the outcome of mycophenolate mofetil combined with low-dose steroids in treating active moderate to severe GO. Methods: In this hospital-based prospective observational longitudinal study, a total of 40 patients with GO were included. Three follow-ups were conducted during the study period. Data were collected using case-record forms and analyzed with SPSS-26. Results: Comparing CAS at 6 months with treatment and baseline CAS shows significant improvement in both eyes (right eye's P value is 0.001 and left eye's P value is 0.025). Spontaneous retro-orbital pain, pain on eye movement, redness, and swelling of the caruncle and conjunctiva significantly reduced over the treatment period, while eyelid swelling showed a slight decrease. Lid retraction and soft tissue involvement improved in both eyes, although changes in diplopia and ocular motility are not statistically significant. Regarding outcome pattern, the majority of participants (68.8%) demonstrated significant improvement, while 31.3% showed unchanged/static. Conclusion: MMF combined with low-dose prednisolone may be considered for the treatment of moderate to severe GO as a steroid-sparing agent. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S40]